Leading with Integrity: Revealing the Nexus in Private Sector Dynamics between Ethical Leadership and Employee Engagement - Younas, Asifa; Saleem, Kashif (Advances in Social Sciences Research Journal, 2024)
With a focus on the south-northern region of the Punjab, Pakistan this quantitative correlational study explores the relationship between work engagement and ethical leadership in private enterprises within a developed geographic area. Based on the theoretical framework of ethical leadership theory by Brown et al. and the conceptual dimensions of work engagement by Schaufeli and Bakker, this study uses survey data from the Ethical Leadership Scale (ELS) and the Utrecht Work Engagement Scale (UWES) to examine 150 conveniently sampled employees. The results, which were obtained using Pearson correlation analysis in SPSS V.24, provide strong evidence against the null hypothesis and show a substantial link between ethical leadership and total job engagement. Furthermore, particular job engagement dimensions—such as vigor, devotion, and absorption—show strong connections with ethical leadership in south-northern private enterprises. As a result, the results highlight the significance of ethical leadership in encouraging higher levels of employee engagement at work, offering insightful information to private enterprises looking to maximize worker productivity and results. In order to favorably impact the many aspects of work engagement and enhance the general well-being and productivity of employees in the private sector, especially in the south-northern region in Punjab, Pakistan the study suggests making strategic investments in ethical leadership.